The Role of Green Bonds as a Financing Solution for Adapting to ESG Regulations and Its Impact on Corporate Profitability - Riswanda, Muhammad Rumi Alvito; Precilia, Tharisa; Tjajadi, Catherine; Fauzi, Fitriya (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
The article